Effect of Continuous Darkness on Immune Response (In vivo Assay) - Al-Joofy, Ikbal Kh.; Al-Khishali, Thana J. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Reports denote that changes in day length enhance or suppress components of immune function in several mammalian species. The aim of present experimental study isdirected to test the hypothesis deals with the effect of photoperiods on some immune limbs responsiveness.Materials and Methods: Twenty six male and female BALB/C mice, 5-7 weeks old, 14- 18gm weight divided into two groups, test groups (n.=8 mice for each sex) and controlgroups (n.=5 for each sex). Test groups were kept in a dark room for a month, while control groups were kept in a room where the photoperiod was day light: darkness 12:12hr. Allstudied groups immunized with o.2ml (10% sheep red blood cells) on day 4 and 8 of the last 12 days of the experiment. The weight of all animals were measured at the beginning and theend of the experiment. Arthus reaction, delayed type hypersensitivity and serum antibody titer were assessed on day 11 and 12 of program.Results: Significant increased (P